Hydrogen-Bonded Conjugated Materials and Their Application in Organic Field-Effect Transistors - Shi, Xin; Bao, Weiwei (Frontiers in Chemistry, 2021)
Recent research on organic semiconductors has revealed that the composition of the constituent organic material, as well as the subtle changes in its structure (the stacking order of molecules), can noticeably affect its bulk properties. One of the reasons for this is that the charge transport in conjugated materials is strongly affected by their structure. Further, the charge mobility increases significantly when the conjugated materials exhibit self-assembly, resulting in the formation of ordered structures. However, well-organized nanostructures are difficult to obtain using classical solution processing methods, owing to their disordered state. A simple strategy for obtaining well-ordered material films involves synthesizing new conjugated materials that can self-organize. Introducing hydrogen bonding in the materials to yield hydrogen-bonded material superstructures can be a suitable method to fulfill these critical requirements. The formed hydrogen bonds will facilitate the assembly of the molecules into a highly ordered structure and bridge the distance between the adjacent molecules, thus enhancing the intermolecular charge transfer. In this minireview, hydrogen-bonded small molecules and polymers as well as the relationship between their chemical structures and performances in organic field-effect transistors are discussed.